2019
DOI: 10.4103/apjon.apjon_19_19
|View full text |Cite
|
Sign up to set email alerts
|

Improving Information Provision on Chemotherapy-Induced Alopecia and Scalp Cooling: A Comprehensive Approach Including A Website and Web-Based Decision Tool

Abstract: Objective: Alopecia is a frequently occurring side effect of chemotherapy and has high impact on many patients. Currently, scalp cooling is the only method to prevent this chemotherapy-induced alopecia (CIA) and it is effective in about half of the patients. Since determinants of the success are largely unknown, all patients should be prepared for potential hair loss. The objective was to provide up-to-date online information about CIA and scalp cooling to support patients in coping with CIA and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…In other cases, such as anthracyclines and cyclophosphamide‐based regimens, use of the device should be considered on an individual patient basis, balancing the lower efficacy rates and the longer duration of chemotherapy administration against the physical and psychological distress patients may experience because of hair loss. In this regard, given the lack of established factors for predicting scalp hypothermia efficacy, we suggest that oncology nurses could assist to ensure a satisfactory result of the entire procedure: monitor the efficacy and the tolerability of the device during each chemotherapy cycle; make sure all the instructions in both preparation and post‐cooling phase are followed (Katz, 2017); properly manage increased chair time and workload; provide EBC patients information about CIA, scalp cooling and its possible side effects through direct nursing consultation and/or web‐based tools (Van Den Hurk, Keizer‐Heldens, Raats, Hoeijmakers, & Mols, 2019) and support their decision about the use of the device.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, such as anthracyclines and cyclophosphamide‐based regimens, use of the device should be considered on an individual patient basis, balancing the lower efficacy rates and the longer duration of chemotherapy administration against the physical and psychological distress patients may experience because of hair loss. In this regard, given the lack of established factors for predicting scalp hypothermia efficacy, we suggest that oncology nurses could assist to ensure a satisfactory result of the entire procedure: monitor the efficacy and the tolerability of the device during each chemotherapy cycle; make sure all the instructions in both preparation and post‐cooling phase are followed (Katz, 2017); properly manage increased chair time and workload; provide EBC patients information about CIA, scalp cooling and its possible side effects through direct nursing consultation and/or web‐based tools (Van Den Hurk, Keizer‐Heldens, Raats, Hoeijmakers, & Mols, 2019) and support their decision about the use of the device.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that patients are not adequately prepared for the potential limited efficacy of, or experiences associated with, SC. In a 2016 qualitative study of 17 women with breast cancer, women reported unmet information needs in regard to the SC process, its side effects and, efficacy (Shaw et al, 2016); findings reiterated in a Dutch study that set out to develop a web-based decision tool for women considering SC during treatment for breast cancer (van den Hurk et al, 2019). In preparing for our study, we were struck by the paucity of qualitative data, and particularly, of recent qualitative or mixed methods publications available to guide and advance evidence-informed preparation of women considering SC during their chemotherapy.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Chemotherapy-induced alopecia is a constant reminder of a cancer diagnosis and can stigmatise a person affected by cancer. SC that prevents or significantly reduces hair loss can lead to improved patient well-being (Choi et al, 2014;van den Hurk et al, 2010).…”
Section: Con Clus I On S and Rele Van Ce To Pr Ac Ti Cementioning
confidence: 99%
See 1 more Smart Citation
“…The Dutch Scalp Cooling Registry has collected data of > 7000 patients since 2006 [ 13 ]. The majority of patients were treated for breast cancer and in a (neo)adjuvant setting.…”
Section: Introductionmentioning
confidence: 99%